Effect of inorganic nanoparticles and organic complexes on their basis on free-radical processes in some model systems - Averchenko, K.A.; Kavok, N.S.; Klochkov, V.K.; Sedyh, O.O.; Yefimova, S.L.; Malyukin, Yu.V. (Вiopolymers and Cell, 2015)
Aim. Evaluation of free–radical activity of rare–earth based nanoparticles (NPs) (orthovanadates and CeO2) with different geometrical parameters, and organic complexes formed on their base with methylene blue (MB) photodynamic dye in abiotic and biotic systems (homogenate of liver, isolated mitochondria and isolated hepatocytes). Methods. Effects of NPs were estimated using luminol-dependent chemiluminescence (ChL) and by measurement of the final product of lipid peroxidation – malondialdehyde (MDA). Results. According to the ChL data in abiotic systems all NPs demonstrated antiradical activity. In biotic systems spherical extra small (1–2 nm) NPs of both types showed prooxidant effects of different degree; CeO2 of 8–10 nm have demonstrated a week antioxidant effect. The data of ChL correlated with the measurements of MDA-level. The effects of «NP-MB» complexes were the same as the corresponding «bare» NPs in different examined systems. The most prooxidant NPs in the presence of glutathione (GSH) did not aggravate free-radical processes. NPs demonstrated a more pronounced prooxidant effect in cells at pH 7.8 that may be a result of pH-dependent changes in protonated GSH. Conclusions. Differences in the effects of NPs in the biotic systems depend on their geometric parameters that determine their penetration and interaction with the cellular structures. This is also related to the processes on the NPs surface as well as in the near-surface layers.